Response of planktonic copepods of the White Sea to the water salinity changes in acute and chronic experiments - Daria M. Martynova (Cherepovets State University, 2020)
In the White Sea, planktonic copepods Calanus glacialis, Pseudocalanus spp., Triconia borealis, and Metridia longa are usually not considered as tolerant to the water salinity decrease, and Oithona similis is generally attributed to the euryhaline species. However, the life cycle of the first two genera includes active feeding during the spring ice melting, when a large part of their food sources are concentrated in the upper water layer characterized by salinity less than 18‰. M. longa and T. borealis are considered to be deep-dwelling species. The first one reproduces in autumn and thus relies on the spring phytoplankton bloom the least, the second spawns in spring in deep water layers; however, they are both found in the productive (photic) layer during this season. In order to study if these copepods can use food-rich freshened water layers to get enough energy for growth and reproduction, a series of experiments were performed in July 2019 and March 2020, including chronic and acute ones. The copepod mortality was analyzed at 25‰ or 26‰ (control), 18‰ and 15‰ (experiment). Surprisingly, C. glacialis and Pseudocalanus spp. stood the salinity decrease with minor mortality rates ranging from 0 up to 1.1 ± 0.2% in short-term 24-h experiments. The mortality rate in these species was the highest after five days of gradual water freshening down to 15‰ (12.1 ± 1.8%), while the mortality rate was half as much in control vials at 25/26‰ and at 18‰ (6.4 ± 0.5% and 6.9 ± 0.6%, respectively). T. borealis was the most stenohaline species, exhibiting the 100% mortality rate already at 18‰ after 2 hours of exposure. M. longa did not tolerate the salinity stress at 15‰, reaching 100% mortality in 24 h. O. similis tolerated the salinity decrease well and thus exhibited euryhaline features as reported for this species in different areas of its range.